STUDENTS’ PERCEPTION TOWARDS THE USE OF VIDEO IN ENGLISH CLASS - Silvia Revansyah; Efransyah (IKIP Siliwangi, 2023)
The aim of this study is to comprehend how students feel about using videos in English classes. The research technique makes use of qualitative research. 32 students completing English lessons participated in this study. The study used a Likert scale, which included two response choices: